2000
DOI: 10.4049/jimmunol.164.2.916
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and Type 2 CD8+ Effector T Cell Subpopulations Promote Long-Term Tumor Immunity and Protection to Progressively Growing Tumor

Abstract: Cytolytic CD8+ effector cells fall into two subpopulations based on cytokine secretion. Type 1 CD8+ T cells (Tc1) secrete IFN-γ, whereas type 2 CD8+ T cells (Tc2) secrete IL-4, IL-5, and IL-10. Using an OVA-transfected B16 lung metastases model, we assessed the therapeutic effects of adoptively transferred OVA-specific Tc1 and Tc2 subpopulations in mice bearing established pulmonary malignancy. Effector cell-treated mice exhibiting high (5 × 105) tumor burdens experienced significant (p < 0.05) delays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 46 publications
4
80
2
Order By: Relevance
“…At 12 days after tumor cell injection, mice had lung micrometastasis. 5 These mice were then treated with i.v. injection of the engineered CD8 þ T TNF and the control CD8 þ T control or 'T þ rTNF' cells (2 Â 10 6 cells per mouse).…”
Section: T-cell Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 days after tumor cell injection, mice had lung micrometastasis. 5 These mice were then treated with i.v. injection of the engineered CD8 þ T TNF and the control CD8 þ T control or 'T þ rTNF' cells (2 Â 10 6 cells per mouse).…”
Section: T-cell Cytotoxicity Assaymentioning
confidence: 99%
“…4 Recently, it has further been reported that adoptive transfer of cytotoxic T type 1 cells can cure 70% palpable tumors. 5 More recently, Becker et al 6 have shown that Tc cells enriched through an interferon (IFN)-g-capture method displayed enhanced tumor-specific cytotoxicity and the adoptive therapy with these T cells cured 3/5 mice bearing 3-day tumors. In most of these animal models, T-cell adoptive therapy is all limited in treatment of earlystage tumors (e.g., 3-day or palpable tumors or 3-10-day early lung metastases), but not large tumors.…”
Section: Introductionmentioning
confidence: 99%
“…To assess such a hypothesis, we monitored the tumor-specific IFN-␥ response in MT/ret melanoma mice and compared it with the response in mice with concurrent vitiligo. Many reports have indicated that IFN-␥ plays a critical role in the development of tumor immunity, and recent reports including ours using IFN-␥ knock-out mice demonstrated a crucial role for IFN-␥ in the control of B16 melanoma growth in vivo (15)(16)(17). To evaluate natural tumor-specific response, ex vivo IFN-␥-ELISPOT assays were performed by using PBLs isolated from MT/ret mice as effector cells and a Melan-ret cell line as melanoma antigen-presenting cells.…”
Section: Treatment With Heavy Metal Leads To Vitiligo Development In mentioning
confidence: 99%
“…[9][10][11] Dutton et al 12 have originally reported that both tumor-specific Tc1 and Tc2 cells can mediate reduction in lung metastasis of B16 melanoma in vivo. Recently, they have further shown that these tumorspecific Tc1 and Tc2 can also cure intradermally transplanted B16 melanomas, but only in their palpable sizes, 13 but Tc1 cells were more effective than Tc2 in controlling tumor growth and in prolonging the survival times of tumor-bearing mice. 14 …”
Section: Cd8mentioning
confidence: 99%